THE RELATIONSHIP BETWEEN FAMILY FUNCTION AND QUALITY OF LIFE IN THE ELDERLY IN BAGELEN VILLAGE - Sulastri, Sulastri; Kohir, Dedek Saiful (Journal of Vocational Nursing, 2021)
Introduction: Efforts to overcome the effects of the aging process are a problem for the majority of the elderly, including those who live with their families. Family has an important role in providing old age with a good quality of life. The quality of life of the elderly is influenced by various factors such as social relationships, social environment, psychological factors, and social activities. This study aims to determine the relationship between family function and quality of life in the elderly. Methods: The research design used was a correlation study, with a cross-sectional approach. The sampling technique used was multistage random sampling, the number of samples was 95 people. Data collection used the World Health Organization's Quality of Life-OLD (WHOQOL-OLD) questionnaire. Results The results showed that there was a relationship between family support using family apgar and the quality of life of the elderly (p = 0.002).  Conclusion: It is recommended for families to provide optimal support by paying attention to the adaptability of the elderly, closeness, development, providing opportunities for the elderly to express feelings, and solving problems for a better quality of life for the elderly.